Urolithiasis in Clinical Practice - Al-Mamari, Said Abdallah (Springer International Publishing : Imprint: Springer, 2017)
This book serves as a concise guide to urinary stone disease, providing simplified and complete information about the topic area. Various surgical techniques are provided and accompanied by first-hand accounts, to give insight into the operating room. The book is a quick reference guide and is relevant to both trainees and professionals. Written by a leading expert in the field, this book brings together years of experience and contains essential information on all aspects of lithology. The book covers all treatment options so that the best possible methods can be chosen for each patient. Urinary stone disease is a widespread ailment and updated information about it is permanently needed by trainees and professionals.
Keywords: Medicine.; Nephrology.; Urology.; Epidemiology.; elektronické knihy; electronic books